Comparing anticholinergic persistence and adherence profiles in overactive bladder patients based on gender, obesity, and major anticholinergic agents. Issue 8 (3rd May 2017) - Lua, Lannah L.; Pathak, Prathamesh; Dandolu, Vani
Abstract : Aims: Overactive bladder (OAB) is highly prevalent particularly among obese patients and significantly impacts quality of life. Anticholinergics are the first‐line treatment. The effect of obesity on medication compliance has not been studied. Our study evaluated gender‐ and obesity‐specific adherence and persistence of anticholinergic medications in OAB. We also compared adherence and persistence on solifenacin to oxybutynin, tolterodine, and all anticholinergics combined. Methods: Truven Marketscan Commercial Claims and Encounter database from 2005 to 2013 was used. OAB patients aged 18‐65 continuously enrolled for ≥12 months pre‐ and post‐index were identified. Adherence was assessed by medication possession ratio (MPR) and proportion of days covered (PDC). Persistence was defined as number of days from anticholinergic initiation to discontinuation, switch, or end of study. Statistical analyses were performed using SAS 9.3. Results: Among 122 641 OAB patients, most common comorbidities were hypertension, depression, and diabetes; patients with these conditions were more compliant. Obese patients were 7% less likely to adhere and 6% more likely to become non‐persistent on anticholinergics compared to non‐obese. Males were 20% more likely to adhere to anticholinergics compared to females. Oxybutynin, solifenacin, and tolterodine were the most common anticholinergics. Solifenacin demonstrated higher adherence and persistence compared to all anticholinergics combined. The proportion of patients still on solifenacin at 1 year was 17.11%, compared to 12.64% for all anticholinergics combined. Conclusions: Men are more likely to be adherent to anticholinergics than women. Obese patients are less likely to be compliant to medications, possibly related to severity of symptoms. Solifenacin had the highest rates of patient compliance.